Sustaining Ophthalmic Practices for the Future: A High-Value Care Approach to Environmental Responsibility - Yee Ling Wong; Tariq M. Aslam; David F. Chang; Barbara Erny (Ophthalmology and Therapy)
Abstract Ophthalmology, like all medical specialities, is continuously evolving to adapt to emerging challenges and advancements. The evidence-based medical practices that previously guided policies and regulations may no longer be sufficient or sustainable in the context of an ageing population, increasing healthcare demands, and the urgent need for sustainability. As the global burden on healthcare systems grows, sustainability must be considered from multiple perspectives, including financial and environmental aspects, without compromising patient outcomes. While financial sustainability is essential to ensure cost-effective resource allocation, accessibility, and affordability for both healthcare providers and patients, environmental sustainability is becoming an increasing priority. Efforts to minimise the carbon footprint associated with medical procedures, transportation, and the production and disposal of ophthalmic equipment and materials are necessary. This paper highlights key examples of areas within ophthalmology where sustainability can be enhanced by practicing high-value care. We describe targeted opportunities that demonstrate how sustainable practices can be successfully integrated into ophthalmology without compromising patient care or operational feasibility.